Estresse percebido de mães de crianças com necessidades especiais de saúde e fatores sociodemográficos relacionados - Paes, Larissa de Cássia Rocha (Universidade Federal de São Carlos, 2023)
Objective: To analyze stress among mothers of children with special health needs and identify related sociodemographic factors. Method: A cross-sectional, quantitative study was conducted with mothers of children with special health needs undergoing follow-up at a medium-complexity outpatient clinic that provides rehabilitation activities for children with conditions affecting neuromotor and sensory development in a municipality in the interior of São Paulo state. Data collection took place remotely between March and July 2021, through the application of a sociodemographic characterization instrument and the Perceived Stress Scale, which scores from zero to 56 points. The following statistical tests were used for data analysis: Mann-Whitney, Kruskal-Wallis, Spearman correlation, and simple and multiple linear regression. Results: 57 mothers participated with a mean age of 34.4 years. The average level of perceived stress was 30.56, with a minimum of 12 and a maximum of 52. Sociodemographic factors associated with stress were: maternal age (p <0.001), marital status (p <0.001), and number of children (p = 0.019). Conclusion: Mothers with a higher level of perceived stress were those who were younger, without a partner, and had a higher number of children.
Perceived stress in mothers of children with special health needs and related sociodemographic factors
Keywords: Enfermagem; Criança; Estresse; Mães; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PEDIATRICA